Motives to engage with sports brands on Facebook and Instagram – the case of a Portuguese football club - Machado, Joana César (2020)
Purpose Social network sites are key marketing tools that allow brands to connect and engage with consumers. However, there is still a lack of evidence of their value for football brands. This research aims to understand the motivations for fans to engage with their favourite football brands on Facebook and Instagram. Design/methodology/approach An online survey was performed, resulting in 214 valid responses. As the social media strategy followed by the football brand analysed was built around games, the authors divided fans into two groups based on the main method in which the club's games are watched: in stadium versus mediated. Multiple linear regression analysis was used to explore the relationship between motivations and fans' engagement, through content consumption and contribution, on Facebook and Instagram. Analysis was performed first with the whole sample and then by group (stadium attendance vs mediated attendance fans). Findings The findings show that social influence, entertainment, searching for information and rewards are the most relevant motivations for consumers to engage with brand-related content on Facebook. Entertainment, rewards and social influence are the main motivations influencing consumer interactions on Instagram. Group moderation was only confirmed in the impact of social influence on Facebook page content consumption. Originality/value The results provide valuable insights into the social media marketing activities of sports brands, which will assist brand managers to develop strategies for effectively stimulating engagement with the different groups of fans.